Morphological Characterization Of Transition Metal Ternary Mosse Chalcogenide Thin Films By Electrochemical Route - Nik Ramli, Nik Suhaini (2020)
Through the performance of the PEC systems in power conversation, it may be possible to build affordable photovoltaic panels. The main reason is to find the right alternative material for the conversion of solar energy. Molybdenum chalcogenide can be used for photovoltaic conversion in thin films as ternary materials for solar cells. This research will focus primarily on using electrodeposition technique to investigate transition molybdenum chalcogenide. Electrodeposition method is one of the methods that belongs to chemical route. This method able to synthesis the thin films at lower cost. Besides, it able to produce the thin films in a large scale which make it attractive for industry. Ternary molybdenum chalcogenide MoSSe was chosen as a material in this study. MoSSe thin films was synthesis through electrodeposition method at various deposition time. Moreover, the thin films are characterizing for its morphological and compositional properties by using SEM and EDX. In addition, the optical properties of the thin films also were observed to study the suitability of the materials for the used in photoelectrochemical cell. Ternary molybdenum chalcogenide of Molybdenum sulphoselenide MoSSe was prepared and ITO glass substrates was used as a substrate. MoSSe were deposited on the ITO glass substrates at different deposition time which are 10 minutes, 20 minutes, and 30 minutes and at the temperature of 40 ℃. The cyclic voltammetry process was taking places to ensure the potential value for the deposition process takes place. Then, the electrodeposition process was proceeding with the selected potential from the cyclic voltammetry. Then, the thin films were examined for its morphological, compositional and its optical properties. It was observed that the potential of the deposition process is at -1.0 V through the cyclic voltammetry process. Thus, the electrodeposition process was occurred at -1.0 V. The scanning electron micrograph reveal that the surface of the films tends to grow as the deposition time increase. In addition, the MoSSe thin films have been proved to be successfully deposited on the substrates as all the elements of Mo, S and Se from the composition analysis. Moreover, from the Mott-scottky plots, it shows that the flat band potential is decreasing upon an increasing of the thickness of the films. The results obtained reveals the suitability of MoSSe as solar cell alternative materials.